X-ray binary stars - Perko, Manica (Matrika, 2021)
A binary system is a system that contains two stars which orbit around the center of mass of the system. In an X-ray binary systems one of the two stars is a very small and dense object called a neutron star. A neutron star is a collapsed core of a star which had a mass of more than 8 solar masses. The mass transfer in a high-mass X-ray binary is driven by strong stellar winds and in a low-mass X-ray binary the mass is transferred via Roche lobe overflow.
Keywords: binarni sistemi; binary systems; stars; zvezde